ANALISIS NILAI DIDAKTIS NOVEL REMAJA APAPUNSELAIN HUJAN KARYA ORIZUKA - Arami, Santi; Sitepu, Tepu (Jurnal Bahastra, 2023)
This study aims to describe the didactic values contained in the youth novel Whatever Apart from Rain by Orizuka. The source of the data in this study was the youth novel Whatever Apart from Rain by Orizuka which totaled 287 pages and was published by Gagas Media. The first print was published in 2016. This research method is a descriptive method using a qualitative approach. Instrument. This research was conducted with documentation guidelines. Data analysis techniques include reading youth novels, collecting data, underlining, describing, and concluding. The research data is in the form of didactic values: tolerance, sharing, helping others, empathy, honesty, the quality of good deeds, authenticity. The results of the research show that there are didactic values: tolerance, sharing, helping others, empathy, honesty, quality of good deeds, authenticity in youth novels Anything But Rain by Orizuka.